Implementasi Internet of Things (IoT) Untuk Sistem Pemantauan Kebakaran Dini Dengan Notifikasi Telegram dan Alarm - Zaenuar Erfandi; Hartanti, Dwi; Maulindar, Joni (Infotek: Jurnal Informatika dan Teknologi, 2025)
Fire is a serious threat that can cause major losses, both material and non-material. This research aims to develop an Internet of Things (IoT) based fire monitoring system at the Tangen District Office to detect fires early. This system uses smoke, temperature and fire sensors integrated with a NodeMCU microcontroller to process data in real-time. Data from sensors is analyzed to detect signs of fire, and notifications are sent instantly via the Telegram application and accompanied by alarm activation. Tests show that the system has a detection accuracy rate of up to 95% in detecting various types of fire media, such as wood, paper and plastic, with an effective sensor distance of up to 20 cm. This system is able to reduce response time by up to 70% compared to conventional methods, increasing the readiness of officers in handling fires. It is hoped that the results of this research can minimize the risk and impact of fire, as well as significantly increase building safety